Performance assessment of ga district mutual health insurance scheme, greater accra region, Ghana - Nsiah-Boateng, E.; Aikins, M. (Value in Health Regional Issues, 2013)
Objective: This study assessed performance of the Ga District Mutual Health Insurance Scheme over the period 2007-2009. Methods: The desk review method was used to collect secondary data on membership coverage, revenue, expenditure, and claims settlement patterns of the scheme. A household survey was also conducted in the Madina Township by using a self-administered semi-structured questionnaire to determine community coverage of the scheme. Results: The study showed membership coverage of 21.8% and community coverage of 22.2%. The main reasons why respondents had not registered with the scheme are that contributions are high and it does not offer the services needed. Financially, the scheme depended largely on subsidies and reinsurance from the National Health Insurance Authority for 89.8% of its revenue. Approximately 92% of the total revenue was spent on medical claims, and 99% of provider claims were settled beyond the stipulated 4-week period. Conclusions: There is an increasing trend in medical claims expenditure and lengthy delay in claims settlements, with most of them being paid beyond the mandatory 4-week period. Introduction of cost-containment measures including co-payment and capitation payment mechanism would be necessary to reduce the escalating cost of medical claims. Adherence to the 4-week stipulated period for payment of medical claims would be important to ensure that health care providers are financially resourced to deliver continuous health services to insured members. Furthermore, resourcing the scheme would be useful for speedy vetting of claims and also, community education on the National Health Insurance Scheme to improve membership coverage and revenue from the informal sector. © 2013 International Society for Pharmacoeconomics and Outcomes Research (ISPOR).
Keywords: Claims settlements; Ghana; Membership coverage; National Health Insurance Scheme